MASS CULTIVATION OF SARPAGANDHA (RAUWOLFIA SERPENTINA BENTH. EX KURZ) IN CONSIDERATION WITH ENVIRONMENTAL FACTORS AND CULTIVATION TECHNIQUES - Mrunalini, *Paturkar; P, Khobragade (International Journal of Ayurveda and Pharma Research, 2016)
Sarpagandha (Rauwolfia serpentina Benth. Ex Kurz.)A perennial medicinal plant of family Apocynaceae is well known as Serpentina root, the natural source of alkaloid reserpine used for the treatment of Hypertension, neuro disorders like psychosis, schizophrenia, insanity, insomnia and epilepsy. It contains alkaloids reserpine, yohimbine, ajmaline, ophioxylin, resin, wax, starch are used as a sedative and tranquilizing agent. Main Ayurvedic products of Sarpagandha are Sarpagandha Ghanvati, Sarpagandha Yoga, Sarpagandha Churna and Mahesvari Vati. The world requirement for dry Sarpagandha roots is around 20,000 t per annum which is a great demand because of its high medicinal value. The internal consumption of dried roots is â‰ˆ150 t per annum. It is the red listed plant and as its germination rate is low and high demand in national and international market, it is necessary to increase its commercial production by using various effective and low cost techniques. This paper is going to through light upon various effective cultivation techniques and environmental factors responsible for growth of plants so that cultivars interest in Sarpagandha cultivation would increase on commercial basis and it will become again a boon for Ayurveda.